Códice 49-VI-3
This historical document transcription, originating from the Jesuit Mission of Tumkin in Macao between 1711 and 1720, forms part of a series of ecclesiastical records compiled by João Alvares and later forwarded to the Procuratorship in Lisbon. The text details missionary activities across contested territories such as Tonkin (Tunkim), Funckim, and Dunkin during periods of intense persecution under royal decrees. It documents the spiritual labours, administrative challenges, and sacramental ministries of Jesuit missionaries including Francisco Nogueira Rodrigues, Father Ruiz, and Father Ignacio Martiny, among others. The narrative highlights efforts to sustain clandestine Christian communities amid political hostility, forced concealment, imprisonment, and martyrdom. Key figures such as Father Marinho Coelho, Father Jerónimo de Azevedo, and Alexandre de Rhodes are noted for their linguistic and pastoral contributions. The abstract includes statistical accounts of conversions, baptisms, and confessions, alongside reports of resistance from local authorities, particularly Mandarins, who enforced prohibitions against Christian practice through edicts, confiscations, and corporal punishment. Despite severe hardship—including famine, illness, and isolation—missionaries continued administering sacraments in secret, often relying on native catechists and covert networks. The document reflects colonial-era religious conflict, indigenous engagement with Catholicism, and institutional struggles within the Society of Jesus, preserved in Portuguese ecclesiastical archives for doctrinal and administrative review.
Keywords: Administrative Challenges; Alexandre de Rhodes; Dunkin; Father Ignacio Martiny; Father Jerónimo de Azevedo; Father Marinho Coelho; Father Ruiz; Forced Concealment; Francisco Nogueira Rodrigues; Funckim; Imprisonment; Jesuit Mission of Tumkin; João Alvares; Linguistic Contributions; Lisbon Procuratorship; Macao; Martyrdom; Missionary Activities; Native Catechists; Pastoral Work; Persecution Under Royal Decrees; Sacramental Ministries; Spiritual Labours; Tonkin; Transcription; clandestine Christian communities